SAT0420 Infection as a Comorbidity in a Cohort of Systemic Lupus Erythematosus Patients from Clinical Immunology Unit – Centro Hospitalar do Porto. (9th June 2015) - Alves, R.F.; Lima, S.; Faria, R.; Machado, A.; Lopes, J.; Costa, R.; Brandão, M.; Vasconcelos, C.
Abstract : Background: Infection is one of the leading causes of morbi-mortality in SLE. This susceptibility might be related to genetic or acquired immune defects of SLE itself or to immunosuppressors. Most infections are from common pathogens, mostly bacteria. Opportunistic infections contribute to mortality in patients with SLE. Infections are a cause of hospitalization in up to 30% of patients. Objectives: To understand the impact of SLE and its therapies in the risk of serious infection in our outpatients cohort. Methods: Out of the 500 SLE patients of our cohort, a retrospective analysis of prospectively collected data of SLE patients that came to the outpatient clinic between Jan-June 2013 was performed. 186 patients' charts with definite 1997 ACR SLE classification criteria were reviewed for duration of disease, immunosuppressors currently or formerly used and occurrence of severe infection (defined as opportunistic and/or those with admission criteria). Statistics analysis: SPSS™ v21.0. Results: 170 (91, 4%) were women, mean age of 45, 9 years, mean follow-up time of 9, 2 years and mean age at diagnosis of 34, 6yr. 61 (32, 8%) patients had at least another autoimmune disease, most frequently Sjögren syndrome (23, 37, 7%) and antiphospholipid syndrome (22, 36, 1%). The main immunomodulators currently or formerly used were: hydroxychloroquine in 167 (89, 8%); steroids in 146 (78, 5%); azathioprine in 50 (26, 9%), methotrexate in 23 (12, 4%); cyclophosphamide in 23 (12, 4%), mycophenolate mophetil in 14 (7, 5%); cyclosporine A in 11 (5, 9%) and rituximab in 7 (3, 8%) patients. There were 30 infections in 23 (12, 4%) patients, 6 (20%) of which opportunistic and the other (80%) required hospital admission. Mean age at first infection was 43, 8 years, with a mean follow-up time of 13, 1 years versus 8, 6 years in patients without evidence of infection ( p 0, 002 ). Five (83, 3%) of the opportunistic infections were caused herpes zooster in 3 (60%) and one lung aspergillosis. Non-opportunistic severe infections were 11 (45, 8%) genitourinary and 4 (16, 7%) respiratory tract. The etiologic agent was identified in 11 (45, 8%) cases; mostly bacteria (10; 90, 9%). Patients with exclusive "skin and bone" SLE had a hazard ratio (HR) for infection of 0, 775 (CI95% 0, 103-5, 816) compared with those with other organ-involvements. The risk of infection by the used of each immunomodulator was: steroids [HR 0, 494, non-significant (n.s.)]; hydroxychloroquine (HR 31, 741, n.s); azathioprine (HR 1, 672, n.s.), methotrexate (HR: 11, 149; CI95%: 1, 779-69, 871); mycophenolate mophetil (HR 1, 131, n.s.); cyclosporine A (HR 0, 863, n.s.); cyclophosphamide (HR 1, 123, n.s.) and rituximab (HR 0, 964, n.s.) Conclusions: Infection is an important comorbidity in SLEs. Herpes zoster virus is nowadays recognized as one of the most common opportunistic infection related to immunosuppression. Infection was more frequent in longer disease time: longer SLE "exposure" bias, and more recent patients live a different SLE management era. SLE patients with "skin and bone" exclusive involvement had lower risk of infection, though not achieving statistical significance. There was no evidence of increased risk of infection with the use of all the immunomodulators, with the exception of methotrexate. Disclosure of Interest: None declared